2001
DOI: 10.1111/j.1550-7408.2001.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of Perkinsus andrewsi n. sp. Isolated from the Baltic Clam (Macoma balthica) by Characterization of the Ribosomal RNA Locus, and Development of a Species‐Specific PCR‐Based Diagnostic Assay

Abstract: A Perkinsus species was isolated from the baltic clam Macoma balthica and an in vitro culture established under conditions described for P. marinus. As reported previously, morphological features remarkable enough to clearly indicate that this isolate is a distinct Perkinsus species were lacking. In this study, regions of the rRNA locus (NTS, 18S, ITS1, 5.8S, and ITS2) of this isolate were cloned, sequenced, and compared by alignment with those available for other Perkinsus species and isolates. Sequence data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 48 publications
(103 reference statements)
8
81
3
Order By: Relevance
“…In addition to the inability of P. qugwadi to enlarge in RFTM and to stain blue black with Lugol's solution, differences in morphology and considerable differences in DNA sequences of the ITS region of the ribosomal RNA gene complex between P. qugwadi and other Perkinsus spp. have been found (Coss et al 2001b, Casas et al 2002. In this study, the size of cultured cells incubated in RFTM increased significantly and the enlarged cells stained with Lugol's solution.…”
Section: Quantitation Of Growthmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition to the inability of P. qugwadi to enlarge in RFTM and to stain blue black with Lugol's solution, differences in morphology and considerable differences in DNA sequences of the ITS region of the ribosomal RNA gene complex between P. qugwadi and other Perkinsus spp. have been found (Coss et al 2001b, Casas et al 2002. In this study, the size of cultured cells incubated in RFTM increased significantly and the enlarged cells stained with Lugol's solution.…”
Section: Quantitation Of Growthmentioning
confidence: 78%
“…Perkinsus parasites of infected Baltic clams Macoma balthica were cultured by Kleinschuster et al (1994) and Coss et al (2001a). The parasite cultured by Coss et al (2001b) was designated as a new Perkinsus species, P. andrewsi.…”
Section: Abstract: Perkinsus Atlanticus · Tapes Decussatus · In Vitrmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the nine genes encoding rhomboid-like proteins in P. marinus have significant phylogenetic similarities with the apicomplexan rhomboids ROM1 and ROM6 and intriguingly early electron microscopy studies revealed the existence of rectilinear micronemes and the presence of a mitochondrion in Perkinsus spp. [70], suggesting that the P. marinus ROM1 and ROM6 localize to these organelles, as in T. gondii.…”
Section: Repertoire In Other Protozoansmentioning
confidence: 99%
“…The species have been associated with mass mortalities of commercially important molluscs (Andrews & Hewatt 1957, da Ros & Canzonier 1985, Goggin & Lester 1987. Six species of this genus -P. marinus, P. olseni, P. atlanticus, P. qugwadi (insertae sedis), P. chesapeaki and P. andrewsi -have been described in molluscs from various parts of the world (Mackin et al 1950, Lester & Davis 1981, Azevedo 1989, Blackbourn et al 1998, McLaughlin et al 2000, Coss et al 2001. Recently, unidentified Perkinsus sp.…”
Section: Introductionmentioning
confidence: 99%